Ecotourism Development Strategy Of Wera Nature Recreation Park (NRP) - Poppy Oktadiyani, Poppy Oktadiyani; Iwanuddin, Iwanuddin; Helwinsyah, Helwinsyah (Forestry Department, University of Muhammadiyah Makassar, 2015)
The Wera Nature Recreation Park (NRP) sustainable nature tourism development requires multi-stakeholder synergy and robust potential resources management, it is necessary to development strategy for an effective conservation area management. The purpose of this study: 1) Knowing the aspects tourism supply of Wera NRP, 2) Knowing the aspects tourism demand of Wera NRP, 3) Analyzing the nature tourism development strategy of NRP Wera, and 4) Knowing the types of nature tourism that can be developed in the NRP Wera. The data analysis method was involves tourism supply-demand analysis and development strategy. Development strategy was located on cell-1 (1,09; 1,33) in Grand Strategy Matrix, meaning that it supports aggressive strategy, i.e. intensive promotion on certain segments especially students and people of age 7 - 35. Based on those results, the development of tourisms are nature panorama, nature phenomenon, wildlife observation, hiking, education and conservation, outbond, religious, and rural tourisms.